Labor Activists and the Coordinator of Online Motorcycle Taxi Drivers (Ojol) in the Solo Raya Region Highlight Regulatory Inequality and Worker Welfare Issues - Alden Wilbert Umbu El Katanna; Akbar Pangestu; Rafiq Athaya; Wahyu Putri Astuti; Aan Widi Mardi Astuti; Farhan Cahya Fuad; Puspaningrum (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to analyze regulatory disparities in labor governance and the welfare conditions of online motorcycle taxi drivers within the gig economy ecosystem, with a specific focus on the local context of the Solo Raya region. The transformation of the digital economy, accelerated by the advancement of platform technologies, has created a new partnership-based employment model that generates legal and social implications for workers. This research employs a descriptive-analytical method with a doctrinal (normative) approach through a literature review of statutory regulations, academic works, and relevant secondary data. The findings indicate that Indonesia’s labor law framework has not yet been able to accommodate the characteristics of employment relations in the digital platform sector, thereby placing drivers in a legal grey area that limits their access to social protection and occupational safety guarantees. From an economic perspective, drivers face income uncertainty due to tariff structures and non-transparent platform algorithm mechanisms. In the local context, labor activists function as advocacy agents who not only articulate workers’ interests but also facilitate collective mobilization, provide assistance on labor issues, and encourage policy dialogue with stakeholders. Their presence, together with community coordinators of ride-hailing drivers, strengthens drivers’ capacity to advocate for normative rights and work welfare. This study underscores the need for regulatory reform that is adaptive to digital work models in order to create a more equitable and sustainable gig economy ecosystem.